Waste incineration industry and development policies in China. (December 2015) - Li, Yun; Zhao, Xingang; Li, Yanbin; Li, Xiaoyu
Highlights: The structure and development status of the waste incineration industry in China are analyzed. The industrial characteristics and competition pattern of the waste incineration industry are discussed. The policy background of the waste incineration industry is studied. The development trend of the waste incineration industry is predicted. Abstract: The growing pollution from municipal solid waste due to economic growth and urbanization has brought great challenge to China. The main method of waste disposal has gradually changed from landfill to incineration, because of the enormous land occupation by landfills. The paper presents the results of a study of the development status of the upstream and downstream of the waste incineration industry chain in China, reviews the government policies for the waste incineration power industry, and provides a forecast of the development trend of the waste incineration industry.